(untitled) (Texas Journal of Philology, Culture and History, 2023)
Punctuation in the Arabic language involves placing specific symbols between words or sentences during writing to indicate points of separation, pauses, beginnings, and different vocal tones and communicative purposes. It facilitates the writer’s comprehension while writing and aids the reader’s understanding during reading. The use of punctuation marks in Arabic began around a hundred years ago when it was introduced from other languages by Ahmad Zaki Pasha, upon the request of the Egyptian Ministry of Education at that time. Over time, additional marks and signals were added. The misuse of punctuation marks can lead to distorting meanings and failing to express intended messages accurately, thus undermining the writer’s purpose. This issue is not limited to writing but extends to vocal expression of the intended meanings represented by these marks . The significance of this research lies in the importance of the Arabic language as a tool for communication and expression, serving as a vital means of understanding among people. Additionally, the importance of correct spelling, as a branch of the Arabic language, allows individuals to express their feelings, thoughts, and identities in written form. Moreover, writing is a crucial skill in the Arabic language, and punctuation marks are essential guidelines for proper writing that convey meanings effectively . The aim of this research is to introduce Arabic punctuation marks, clarify their functions and positions, and emphasize their necessity. The research is structured into an introduction and three sections, concluding with a conclusion and a list of sources used to enrich its content.